CORRESPONDENCE BETWEEN OBJECTIVE AND SUBJECTIVE MEMORY IS STABLE ACROSS AGE. (11th November 2018) - Freed, S; Sprague, B; Ross, L
Abstract: Self-reported memory is commonly used in clinical and research settings with older adults. However, often there is weak or no correspondence between older adults' subjective and objective memory, suggesting that other variables may play a role in this relationship. Depression, gender, and education, and age influence the association between subjective and objective memory; however, prior research on the role of age is mixed and has been constrained to linear or quadratic age differences. Time-varying effects modeling is a novel statistical technique that does not impose linearity assumptions, allowing researchers to explore how the magnitude of the relationship between two variables differs across time. Using cross-sectional age in years as the time-varying metric, we examined the relationship between subjective (Memory Function Questionnaire) and objective memory (composite: AVLT and HVLT) in a sample of 2802 healthy community-dwelling older adults aged 65 and older (M=73.63, SD=5.90, 75.9% female, 72.7% White). After controlling for gender, depressive symptoms, and education, the association between objective and subjective memory was significant and fairly stable (b = 0.2; range = 0.13 to 0.22, p < .05) across ages 65 to 90. Men (b = 0.14) and participants with fewer depressive symptoms (b = -0.04), and more years of education (b = 0.02) had better self-reported memory. Consistent significant but weak correspondence between self-report and objective memory across older adulthood suggests that participant age is not a marker of the accuracy of self-reported memory reflecting objective memory in clinical and research settings.